RECONSTRUCTION OF THE REGULATION OF CIVIL RELATIONSHIPS OF CHILDREN BORN OUT OF WEDDING TOWARDS THEIR BIOLOGICAL FATHERS POST CONSTITUTIONAL COURT DECISION NUMBER 46/PUU-VIII/2010 - Mohammad Raja Avatar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Children born out of wedlock face structural discrimination in the Indonesian legal system, particularly due to the provisions of Article 43 paragraph (1) of Law Number 1 of 1974 concerning Marriage, which limits the civil relationship of the child only to the mother and her family. Constitutional Court Decree Number 46/PUU-VIII/2010 emerged as a legal breakthrough that recognizes the civil relationship between children born out of wedlock and their biological fathers based on scientific evidence. However, the decision is declaratory in nature without being accompanied by adequately implementing norms, resulting in a systemic normative gap in practice. This study aims to identify the forms of normative gaps in the regulation of the decision and to formulate the necessary legal reconstruction to establish a fair civil relationship between children born out of wedlock and their biological father. The research uses a normative juridical method with a Legislation Approach, Case Approach and Conceptual Approach. The research results indicate that the legal vacuum includes the absence of a standard biological proof mechanism, unclear scope of civil rights, weak institutional coordination, as well as disharmony with the Islamic inheritance law system. Comprehensive legal reconstruction through the revision of the Marriage Law and the establishment of implementing regulations becomes a necessity to achieve substantive justice for children born out of wedlock.